Peran Media Baru Dalam Kegiatan Hijrah Fest - Amelia, Firdhausy; Kamalludin, Kamalludin; May Syarah, Maya (KOMUNIKA, 2020)
The birth of new media in today's digital era adds to the variety of existing social media. One of them is Instagram, social media which was initially used only personally to upload photos or videos, now has many roles that are mostly used by young people or the millennial generation. The Hijrah Fest activity, which has a segmentation of visitors to the younger generation, utilizes and optimizes the use of Instagram social media to support its activities. Therefore, in this study, he wanted to find out what roles the new media had in the Hijrah Fest activities. The research method used is qualitative, with in-depth interview data collection techniques with social media managers Hijrah Fest. From the results of observations, interviews, and documentation, the main role of new media on the hijrahfest Instagram social media is preaching. In addition, in supporting the Hijrah Fest activities, his Instagram account acts as the delivery of information related to the event, communication between the Hijrah Fest to the public, and buying and selling transactions from exhibition stands to visitors.AbstrakLahirnya media baru di era digital saat ini, menambah beragamnya media sosial yang ada. Salah satunya ialah instagram, media sosial yang pada awalnya sebatas digunakan secara personal untuk mengunggah foto atau video, kini memiliki banyak peran yang lebih banyak digunakan oleh anak muda atau generasi milenial. Kegiatan Hijrah Fest yang memiliki segmentasi pengunjung pada generasi muda, memanfaatkan serta mengoptimalkan penggunaan media sosial instagram dalam menunjang kegiatannya. Oleh karena itu, dalam penelitian ini ingin mengetahui apa saja peran yang dimiliki oleh media baru, dalam kegiatan Hijrah Fest. Metode penelitian yang digunakan ialah kualitatif, dengan teknik pengambilan data wawancara mendalam bersama pengelola media sosial Hijrah Fest. Dari hasil observasi, wawancara, dan dokumentasi, peran utama dari media baru pada media sosial instagram hijrahfest ialah berdakwah. Selain itu, dalam menunjang kegiatan Hijrah Fest akun instagramnya berperan sebagai penyampaian informasi terkait acaranya, komunikasi antara pihak Hijrah Fest kepada publik, dan transaksi jual beli dari stand pameran kepada pengunjungnya.